2010
DOI: 10.1177/1359105309355338
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Social Support and Coping Strategies in Predicting Breast Cancer Patients’ Emotional Well-being

Abstract: The goal of the current study was to examine how social support and coping strategies are related in predicting emotional well-being of women with breast cancer. In achieving this goal, we examined two hypothesized models: (1) a moderation model where social support and coping strategies interact with each other in affecting psychological well-being; and (2) a mediation model where the level of social support influences choices of coping strategies between self-blame and positive reframing. In general, the dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

21
140
3
6

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(170 citation statements)
references
References 40 publications
21
140
3
6
Order By: Relevance
“…However, some other sources of support showed a diverse effect on coping behavior of the patients. The current study results were confirmed by the results of other studies [26][27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…However, some other sources of support showed a diverse effect on coping behavior of the patients. The current study results were confirmed by the results of other studies [26][27][28][29].…”
Section: Discussionsupporting
confidence: 91%
“…In addition, several potentially modifiable psychological factors related to individual coping skills of CRC survivors were identified as relevant candidate HRQoL predictors. By influencing stress responses and ego defense mechanisms following major life events, such as a cancer diagnosis, these factors can contribute to the development of psychosomatic symptoms (e.g., fatigue, anxiety and depression) [87][88][89]. Interventions focusing on coping skills of CRC survivors in response to significant health stressors (e.g., cancer diagnosis/treatment, presence of a stoma or multimorbidity) may be a promising strategy to safeguard at-risk individuals against HRQoL deterioration [90].…”
Section: Discussionmentioning
confidence: 99%
“…None the less, they were of the opinion that interacting with other breast cancer survivors in an exercise group could have contributed even more to their social wellness. Effective interventions might rely on breast cancer patients' access to social support 49 . This speaks to implementing a social aspect in future exercise interventions for women during breast cancer treatment.…”
Section: Discussionmentioning
confidence: 99%
“…This resulted in a more structured moderator style and higher degree of control, and might have prevented the participants from pursuing topics of their own interest 24 . The production of focused interaction is the goal of the focus group method, thus the methodological weaknesses in generating the data in this study can be linked to both the role of the moderator, and how the group itself affect the data 49 .…”
Section: Limitationsmentioning
confidence: 99%